Dramaturgy Formation and Development of the Turkic Peoples in the North Caucasus Region - Shapauov А.К. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This article examines the emergence and development of dramatic works among the Turkic peoples of the North Caucasus, including the Nogai, Karachay, Balkar, Gagauz, Kumyk, and Crimean Karaites. It analyzes the formation of early small-scale dramatic forms, their recording in manuscripts, the appearance of genres, and the beginnings of stage art within these communities. Particular attention is given to the artistic level and content of early plays, their cultural and spiritual ties with the Kazakh people, and the transmission of national-ethnic ideas through dramaturgy and theater. The study employs contemporary theoretical and methodological approaches in dramaturgy and theater studies to explore genre features, conflicts, characters, and artistic methods. It also addresses stage representation, acting techniques, and the specifics of theatrical interpretation in comparative perspective. The connection between manuscript traditions and modern professional theater is discussed within a new scientific paradigm. The article emphasizes the significance of Turkic dramaturgy and theater in fostering cultural interaction and highlights the lack of international, interstate-level research on this subject.